Methicillin-resistant Staphylococcus aureus (MRSA) clonal replacement in a Malaysian teaching hospital: findings from an eight-year interval molecular surveillance - Ismail, Mohd Azrul Hisham; Kamarudin, Norhidayah; Abdul Samat, Muttaqillah Najihan; Raja Abdul Rahman, Raja Mohd Fadhil; Saimun, Saberi; Tan, Toh Leong; Neoh, Hui-min (Multidisciplinary Digital Publishing Institute, 2021)
Periodical surveillance on nosocomial pathogens is important for antimicrobial stewardship and infection control. The first methicillin-resistant Staphylococcus aureus (MRSA) molecular surveillance in Hospital Canselor Tuanku Muhriz (HCTM), a Malaysian teaching hospital, was performed in 2009. The dominant clone was identified as an MRSA carrying SCCmec type III-SCCmercury with ccrC and sea+cna toxin genes. In this study, we report the findings of the second HCTM MRSA surveillance carried out in 2017, after an interval of 8 years. Antibiotic susceptibility testing, SCCmec, toxin gene, and spa typing were performed for 222 MRSA strains isolated in 2017. Most strains were resistant to ciprofloxacin, erythromycin, clindamycin, cefoxitin, and penicillin (n = 126, 56.8%), belong to SCCmec type IV (n = 205, 92.3%), spa type t032 (n = 160, 72.1%) and harboured seg+sei toxin genes (n = 172, 77.5%). There was significant association between resistance of the aforementioned antibiotics with SCCmec type IV (p < 0.05), t032 (p < 0.001), and seg+sei carriage (p < 0.05). Results from this second MRSA surveillance revealed the occurrence of clonal replacement in HCTM during an interval of not more than 8 years. Investigation of the corresponding phenotype changes in this new dominant MRSA clone is currently on-going.